DEVELOPMENT OF INNOVATIVE TECHNOLOGIES INMODERN MANUFACTURING OF SPECIAL FOOTWEAR - Ващук, Н. Ф. (Fashion Industry, 2020)
The author of this paper suggests directions of introduction of innovative technologies in production of modern special footwear. However, it is emphasized that the research results have the potential to apply innovative technologies in special footwear. It is noted that innovative footwear manufacturing technologies apply not only to the design, equipment, but also to the use of the latest footwear materials, lining, intermediate materials and soles, connection method and execution technologies. Purpose. The purpose of this work is to highlight the diversity of innovative technologies in the modern production of special footwear, based on the theoretical analysis, with some practical examples in the fi eld of industrial production and publications. Methodology. A systematic approach to the study of the studied objects was used. The objects are innovative technologies in modern production, which consider the design features of footwear that can be introduced in the manufacture of special footwear. During the research, the following methods were used: analysis and review. Results and conclusions. The results and conclusions of the study showed the promising implementation of innovative technologies in footwear. On the basis of the research, it will be the time to develop models of special footwear with the integration of innovative technologies into textiles, leather and other materials. Shoes with innovative technologies change the perception of special footwear and open to people new ways of expression. Due to this, a person will not only be able to show his creativity by changing the design of their shoes in real time, but also more likely to save their lives Practical value. Research results can be used to improve the process of designing and manufacturing special footwear for employees of the National Police of Ukraine, the National Guard of Ukraine, and other military formations.